Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2017)
A dataset containing 102 species occurrences available in GBIF matching the query: { "and" : [ "Geometry POLYGON((-4.037475 47.730087,-3.997306 47.735398,-3.943748 47.729625,-3.935852 47.705140,-3.981857 47.689428,-4.022369 47.690352,-4.043998 47.709299,-4.037475 47.730087))", { "or" : [ "HasGeospatialIssue is false", "HasGeospatialIssue is true" ] } ] } The dataset includes 102 records from 10 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0061029-160910150852091/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences